MENINGKATKAN KONEKSI MATEMATIS SISWA SMP MELALUI PENDEKATAN OPEN-ENDED DENGAN SETTING KOOPERATIF TIPE NHT - Abu Muchlis; Elis Siti Komara; Wiwi Kartiwi; Nurhayati Nurhayati; Heris Hendriana; Wahyu Hidayat (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The problem raised in this research is that students' ability in making mathematical connections is still relatively low. This is because some of the theories in the learning of teachers still enjoy this way of learning, meaning that the students are only recipient of information without inspiration to active. Therefore, the authors are interested to conduct research by applying an NHT cooperative model setting to improve mathematical connection ability of junior high school students. This study aims to determine whether the knowledge of mathematical connections of junior high school students using learning methodology is better than junior high school students using ordinary learning. This research was conducted in SMP Krida Utama Padalarang Class VII, with research method the research used is quasi-experimental method. The sample of this research is taken two classes namely class VII A as experiment class and class VII B as control class. The research instrument is a set of mathematical connection test questions consisting of 5 test questions, and then tested by using a statistical test of differential. Based on the results of research and data processing, the authors conclude that the ability of mathematical connections of junior high school students whose learning using open-ended approach with learning model setting NHT type cooperative learning is better than the mathematical connection ability of junior high school students whose learning using ordinary learning.